The use of Traditional Games to Increase Interest in Learning Multiplication in Class 4 Primary School Students in the City of Bandung - Pratiwi, Intan Aprilianti; Dallyono, Ruswan; Kurniawan, Dede Trie; Yuniarti, Yeni (Universitas Muhammadiyah Mataram, 2025)
Learning multiplication is challenging for fourth-graders of an elementary school in Bandung in terms of the subject when they learn it at school. Some students exhibit no curiosity in mathematics, despite the fact that curiosity is a significant part of learning effectively. This study aims to examine students’ responses on the use of traditional games as a way to grip the minds of pupils in learning multiplication with creative and constructive methods. With the use of the case study approach, the findings are presented through a descriptive analysis through a number of tables which are made from the responses to the questionnaires. The subjects were 30 fourth-grade students. The data were collected through questionnaires and documents with the help of the descriptive statistical methods for the analysis to represent the results in numerical and tabular formats. The conclusion drawn from the research is that the dakon game, the most traditional one, as a learning medium was perceived to be able to bring a remarkable change in students' interest to learn multiplication.